Summer mung: A pathway to sustainable intensification in Sawai Madhopur, Rajasthan - Sharma, Nupur; Meena, B. L. (Indian Farming, 2025)
In many parts of Rajasthan, Haryana, western Uttar Pradesh, and Madhya Pradesh, monocropping of pearl millet or mustard remains a dominant practice, particularly under limited water availability. Districts like Alwar, Dholpur, and Karauli account for a large share of pearl millet cultivation, while Sawai Madhopur shows a moderate share due to its sandy loam soils, moderate rainfall, andpresence of oilseeds, pulses, and spices in the cropping system. Rajasthan ranks first in India for oilseed cultivation, with Sawai Madhopur recording the highest proportion among all districts. Similarly, the state contributes the largest share to national production of both pearl millet and mustard. However, prolonged monocropping has reduced soil fertility, resource use efficiency, and system resilience, highlighting the urgent need for diversification. Interventions such as introducing summer mungbeanthrough cluster frontline demonstrations have shown promising results. Improved varieties like IPM 2-14, IPM 205-7, and MH-1142 not only enhanced productivity but also facilitated significant horizontal spread across Sawai Madhopur district. These outcomes emphasize that integrating shortduration legumes into traditional systems can improve soil health, boost farm income, and enhancesustainability of Indian farming under changing climatic conditions.